Exploring the Impact of Religiosity, Self-Efficacy, Competence, and Achievement Motivation on Teachers' Learning Performance - Santoso Santoso; Supriyono Supriyono; Ishak Maulana; Abd Latif Bustami (STAI Hubbulwathan Duri, 2024)
This research scrutinizes the challenges surrounding establishing learning tutors within the State Civil Apparatus (ASN) and their impact on educational performance. With a sample of 508 respondents selected through stratified random sampling from a population of 1986 tutors in Indonesia, the study employs path analysis to investigate the direct and indirect influences of religiosity, self-efficacy, competence, and achievement motivation on learning performance. The results indicate significant positive effects: religiosity, self-efficacy, and competence independently impact learning performance, with achievement motivation mediating these relationships. The combined influence of religiosity, self-efficacy, competence, and achievement motivation positively affects learning performance, constituting a 42.1% explanatory power, leaving 57.9% unexplored. Practical implications include recommendations for learning tutors to enhance religiosity, self-efficacy, competence, and achievement motivation for improved performance. Institutional support should prioritize competence development, recognizing its pivotal role. Policymakers in education are urged to address the distinct challenges tutors face, necessitating policy adjustments. Future research involves exploring additional factors contributing to the unexplored 57.9% influence on learning performance, advancing the nuanced understanding of this intricate relationship.